Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.gde.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Systematic approaches to identify functional lncRNAs

Abstract: Long noncoding RNAs (lncRNAs) were discovered in eukaryotes more than thirty years ago [1]. Recent advances in genomics have led to the discovery that lncRNAs are transcribed pervasively across the genome [2–5]. There are an increasing number of reports that identify lncRNAs whose expression is modulated during cell differentiation or in disease states. However, biological functions for the vast majority of them are yet to be determined. Here, we propose two ways to identify lncRNAs that have biological functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…We show here that systematic analysis of pairwise GIs can provide insights about the function of individual lncRNAs. The functional maps obtained by GIs could complement the information derived by other high-throughput approaches [76, 77] to help unravel the biological significance of lncRNAs. Although the present study focuses on stable lincRNAs, future work could also analyse GIs for yeast antisense lncRNAs since methodologies are being developed that abrogate the transcription of a specific non-coding RNA without disrupting the expression of its associated sense mRNA [78].…”
Section: Discussionmentioning
confidence: 99%
“…We show here that systematic analysis of pairwise GIs can provide insights about the function of individual lncRNAs. The functional maps obtained by GIs could complement the information derived by other high-throughput approaches [76, 77] to help unravel the biological significance of lncRNAs. Although the present study focuses on stable lincRNAs, future work could also analyse GIs for yeast antisense lncRNAs since methodologies are being developed that abrogate the transcription of a specific non-coding RNA without disrupting the expression of its associated sense mRNA [78].…”
Section: Discussionmentioning
confidence: 99%
“…Among these noncoding RNAs, the long noncoding RNAs (lncRNAs) had more than 200 nt length and could not code proteins, and exerted diverse functions such as cell proliferation, cell apoptosis, angiogenesis, and tumor metastasis. 6 Growing evidence has shown the importance of lncRNA in human diseases, particularly in cancers. Recently, lncRNAs were identified to be associated with the pathogenesis of PE.…”
Section: Introductionmentioning
confidence: 99%
“…The genome‐sequencing projects showed that more than 90% of the genome is transcribed into noncoding RNAs. Among these noncoding RNAs, the long noncoding RNAs (lncRNAs) had more than 200 nt length and could not code proteins, and exerted diverse functions such as cell proliferation, cell apoptosis, angiogenesis, and tumor metastasis . Growing evidence has shown the importance of lncRNA in human diseases, particularly in cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the structure of mRNAs, lncRNAs have a poly tail and promoter structure after splicing [ 10 ]. Since lncRNAs and mRNAs have certain similarities and both have biological functions [ 11 ], the identification and differentiation of lncRNAs and mRNAs deserve further study. Moreover, previous studies have shown that some lncRNAs expressed with high abundance are poorly conserved, while some low-expressed lncRNAs have important functions [ 12 ].…”
Section: Introductionmentioning
confidence: 99%